Biebrich Scarlet Biodegradation Optimization Using Response Surface Methodology (Journal of Environmental Microbiology and Toxicology, 2020)
The study was carried out to isolate bacterial strain potential for decolourizing the azo- dye Biebrich Scarlet and to optimize the dye decolourisation using Response Surface Methodology (RSM). From azo- dye screening, five isolates were capable of decolourising Biebrich scarlet and out of these, isolate 33 shows the highest decolourisation rate of 4.9x10-6 mgml-1min-1 compared to the other four. Response Surface Method (RSM) which includes Central Composite design (CCD) was employed following a screening procedure as such the Plackett- Burman design to attain optimal condition in order to achieve full azo- dye Biebrich scarlet decolourisation. Seven variables; pH, temperature (Â°C), ammonium acetate (%), glucose (%), salinity (%), yeast (%) and dye concentration (ppm) were studied. From Plackett- Burman design, four of these variables were chosen for further optimisation. Out of 30 individual runs of CCD, three variables; dye concentration, pH and yeast excluding ammonium acetate showed significant model terms (P-value < 0.05). Morphological identification was carried out on isolate 33 and results predicted that the isolate was a Gram-negative bacterium with catalase and cytochrome oxidase enzymes. This isolate gave a gamma hemolysis on blood agar medium and it decolourises Biebrich scarlet better in a minimal oxygen condition. The optimum ranges expected for a maximum dye decolourisation from this study were ammonium acetate (%) of 0.310.60; dye decolourisation (ppm) of about 112.16 or less; pH of 6.62-7.38 and yeast (%) of 0.23- 0.37. The significance of this study is to isolate, screen and identify the best isolated bacterial strain capable of decolourising Biebrich scarlet azo- dye, to study on the factors promoting the growth and the decolourisation of azo- dye by the isolated bacterium through means of RSM and to estimate the optimum condition in the factors which has a significant effect on the decolourisation percentage.
Keywords: Biebrich Scarlet, RSM, Plackett- Burman, biodegradation, decolourisation